What bears teach us - Elmeligi, Sarah (Rocky Mountain Books Ltd., 2020)
A lavishly illustrated book that explores the complex behavioural characteristics of North America's largest land carnivores by examining the bear-human relationship from the bear's perspective. From the first moment Sarah Elmeligi came eye to eye with a grizzly bear, her life changed. In a moment that lasted mere seconds, she began to question everything she thought she knew about bears. How could this docile creature be the same one with a fearsome reputation for vicious attacks? Through years of research, Elmeligi grew to appreciate that bears are so much more than data points, stunning photos, and sensational online stories. Elmeligi expertly weaves the science of bear behaviour with her passionate account of personal encounters. Dive into the life of a bear biologist as Sarah's colleagues recount their own "stories from the field" -- intimate moments with bears where they were connected to an animal with personality, decision-making capabilities, and a host of engaging behaviours. Join Elmeligi and Marriott on a journey that examines and shares the behaviour of black, grizzly, and polar bears in North America in a way you've never seen before. What Bears Teach Us will surprise you, inspire you, foster your curiosity, and teach you something new about bears and maybe even yourself.